Study of feminicide in the story «Un marido feroz» by Ricardo Palma - Sánchez Rojas, Jennifer Kiara (2022)
In this article, it will be carried out an analysis, from a psychological point of view, of the story «Un marido feroz», which narrates a femicide that took place in Arequipa in 1841, and which is found in the section «Hilachas» of the work Tradiciones peruanas, written by Ricardo Palma. In the first place, we are interested in explaining what is an intimate femicide? and its evolution through the years; at the same time, it will be exposed the unhealthy patterns of behavior that lead a partner or ex-partner to be a victim of this type of violent death. On the other hand, it seeks to educate and empower the female population, to stop these toxic behaviors, thus preventing gender violence from continuing to expand as it has done so far in our country.